2016
DOI: 10.1007/s00586-016-4416-5
|View full text |Cite|
|
Sign up to set email alerts
|

A new dynamic six degrees of freedom disc-loading simulator allows to provoke disc damage and herniation

Abstract: Purpose The cause of disc herniation is not well understood yet. It is assumed that heavy lifting and extreme postures can cause small injuries starting either in the inner anulus or from the outside close to the endplate. Such injuries are accumulated over years until its structure is weakened and finally a single loading event leads to a sudden failure of the last few intact lamellae. This paper describes a novel, custom-developed dynamic 6-DOF discloading simulator that allows complex loading to provoke suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…The rongeur only grasps tissue and does not cut through it; therefore, the volume of tissue sequestered from each respective individual is only predictable within a range. While AF tissue was not specifically identified as part of this procedure, the NP:AF ratio of such a sequester is typically 1:1, based on previous findings of sequester tissue composition [25,30]. Six weeks post-injury, all investigated segments show a resealed dorsal AF with obvious tissue irregularities as shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The rongeur only grasps tissue and does not cut through it; therefore, the volume of tissue sequestered from each respective individual is only predictable within a range. While AF tissue was not specifically identified as part of this procedure, the NP:AF ratio of such a sequester is typically 1:1, based on previous findings of sequester tissue composition [25,30]. Six weeks post-injury, all investigated segments show a resealed dorsal AF with obvious tissue irregularities as shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…AF failure can be seen as a hybrid of local tearing of individual fibers and slippage of overstretched fibers from the main loading zone [23]. From recent in vitro and clinical studies, two typical types of herniation have been defined: mid-span failures and endplate junction failures [23][24][25]. Awl penetration of the AF requires approximately 5 s, comparable to the mid-span failure time of disc herniation triggered by body motion [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Col1a1, Col3a1, Col4a1, and Col5a1) in the IVDs at a juvenile stage of development (P20). Increased expression of fibrillar collagens and induced stiffness of the IVD is expected to result in disturbed stress distribution of the IVD, concentrate loading at the cartilaginous endplate, which increase the risk of endplate fractures and the formation of disc herniations (Adams et al, 1996;Vergroesen et al, 2015;Wilke et al, 2016). The adult IVD is thought to be an avascular tissue, as such its major source of nutrient flux occurs via diffusion through endplate (Urban et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The stiffness and phase results were consistent between the sine and triangle waveforms, suggesting that it may not be necessary to use both waveforms in future tests that adopt the standardized protocol. Sine waveforms are commonly used in spine testing to simplify test control, and approximate physiologic motion (Amin et al, 2015;Chamoli et al, 2015;Costi et al, 2008;Wilke et al, 2016), though triangle waves have also been adopted in position controlled tests to ensure a uniform test rate (Bennett and Kelly, 2013;Gardner-Morse and Stokes, 2004;Holsgrove et al, 2015a;Kotani et al, 2006). However, triangle waveforms may be less applicable in load control testing where the test rate will vary according to the stiffness of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…There are many six-axis testing systems that have been used for the biomechanical testing of the spine (Chung et al, 2002;Ding et al, 2014;Holsgrove et al, 2014;Ilharreborde et al, 2010;Kelly and Bennett, 2013;Martínez et al, 2013;Stokes et al, 2002;Wilke et al, 1994;Wilke et al, 2016), however, the designs and control capabilities of those testing systems vary considerably. Additionally, despite previous studies having demonstrated the large changes in the mechanical properties of spinal specimens due to a preload (Gardner-Morse and Holsgrove et al, 2015a;Panjabi et al, 2001;Tawackoli et al, 2004) and the method of preload application (Cripton et al, 2000), testing rate (Costi et al, 2008;Gay et al, 2008), and testing environment (Costi et al, 2002;Pflaster et al, 1997;Wilke et al, 1998a), the standardization of in-vitro methods is still lacking, despite previous recommendations (Goel et al, 2006;Wilke et al, 1998b), which often makes it difficult, if not impossible, to compare different biomechanical studies (Holsgrove et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%